DIFFERENCES IN COLD SENSITIVITY BETWEEN PASSION FRUIT CULTIVARS DURING POSTHARVEST STORAGE (Nativa, 2025)
Due to the high perishability of passion fruit in ambient conditions, refrigeration is recommended during its transport and storage. However, as a tropical crop, passion fruit is sensitive to temperatures below 6 °C, developing chilling injury symptoms. Considering that sensitivity to this physiological disorder depends on genetic material, this study investigated the susceptibility of the passion fruit cultivars BRS Gigante Amarelo and BRS Sol do Cerrado to cold injury during refrigerated storage. Fruits of both cultivars, harvested at the yellow-green maturity stage, were stored at 4 °C and 10 °C for up to 17 days. Symptoms of chilling injury manifested as the rapid wilting of the fruits. Cv. BRS Sol do Cerrado was particularly temperature-sensitive, exhibiting signs of frostbite. In contrast to what was observed in cv. BRS Gigante Amarelo, the percentage of wrinkled surface, weight loss, titratable acidity, and respiratory rate of cv. BRS Sol do Cerrado was higher at 4 °C than at 10 °C. Our results show distinct responses between the two passion fruit cultivars to refrigeration temperature, with cv. BRS Sol do Cerrado is more sensitive to chilling injury-inducing temperatures than cv. BRS Gigante Amarelo.Keywords: chilling injury; Passiflora edulis; physico-chemical quality. Diferenças na sensibilidade ao frio entre cultivares de maracujá durante o armazenamento pós-colheita ABSTRACT: Devido à elevada perecibilidade do maracujá em condições ambientais, recomenda-se a refrigeração durante o transporte e o armazenamento. Entretanto, por ser uma cultura tropical, o maracujá é sensível a temperaturas abaixo de 6 °C, desenvolvendo sintomas de injúria por chilling. Considerando que a sensibilidade a esse distúrbio fisiológico depende do material genético, este estudo investigou a suscetibilidade das cultivares de maracujá BRS Gigante Amarelo e BRS Sol do Cerrado à injúria por chilling durante o armazenamento refrigerado. Os frutos foram colhidos no estádio verde-amarelo de maturação, armazenados a 4 °C e 10 °C por até 17 dias. Os sintomas de injúria por frio se manifestaram com o rápido murchamento dos frutos. A Cv. BRS Sol do Cerrado foi particularmente sensível à temperatura, apresentando sinais de congelamento. Ao contrário do observado na BRS Gigante Amarelo, a porcentagem de superfície enrugada, a perda de peso, a acidez titulável e a taxa respiratória da BRS Sol do Cerrado foram maiores a 4 °C do que a 10 °C. Nossos resultados demostram respostas diferentes à temperatura de refrigeração, sendo que a cv. BRS Sol do Cerrado sendo mais sensível a temperaturas indutoras de injúria por frio do que a cv. BRS Gigante Amarelo.Palavras-chave: injúria por chilling; Passiflora edulis; qualidade físico-química.